The parent-doctor-child triangle: a structural equation modeling-based study in pediatric outpatient clinics in Indonesia - Areta Idarto; Ferdi Antonio (Child Health Nursing Research)
Purpose Parental satisfaction is essential for evaluating pediatric care quality and influences healthcare practices and performance. Pediatric patients frequently experience anxiety, affecting their and their parents’ satisfaction. Nurses play a key role in reducing anxiety and improving care interactions. Meeting parents’ expectations shapes long-term outcomes and impacts the hospital’s reputation. While instruments such as the Child ZAP (Zufriedenheit in der Arztpraxis) provide comprehensive measures of satisfaction, their use in Indonesia has not been explored. This study aimed to validate the Child ZAP and offer insights to improve pediatric care quality in Indonesia. Methods A cross-sectional study was conducted with 139 mothers whose children were older than 5 years and received treatment at private hospitals. Structured questionnaires were analyzed using partial least squared-structural equation modeling in SmartPLS 4, and a disjoint two-stage method was used to test dimensionality. Results All hypotheses were significant (p<.05), demonstrating strong support. All Child ZAP dimensions, treated as lower-order constructs, effectively measured parents’ satisfaction as a higher-order construct. Overall parental satisfaction significantly influenced behavioral intention and mediated its relationship with Child ZAP. The mother’s and the child’s age served as moderating factors. The research model exhibited strong predictive power, underscoring pediatric nurses’ pivotal role in improving communication among parents, physicians, and children to ensure quality care. Conclusion The Child ZAP instrument effectively evaluates parental satisfaction by examining how children interact and communicate with medical staff. It assesses doctors’ engagement with children and their communication skills, highlighting nurses’ essential role in providing family-centered pediatric care.